2005
DOI: 10.1007/11499053_2
|View full text |Cite
|
Sign up to set email alerts
|

XP South of the Equator: An eXPerience Implementing XP in Brazil

Abstract: Abstract. Many have reported successful experiences using XP, but wehave not yet seen many experiences adapting agile methodologies in developing countries such as Brazil. In a developing economy, embracing change is extremely necessary. This paper relates our experience successfully introducing XP in a start-up company in Brazil. We will cover our adaptations of XP practices and how cultural and economical aspects of the Brazilian society affected our adoption of the methodology. We will discuss how we manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…Several authors reported on advantages of constant code refactoring: ensuring readability and understandability of the code [82], improving modularity [80] and providing discipline to developers [93]. On the other hand, introducing refactoring may cause problems since developers had no or little experience [63] and they didn't see immediate value in introducing high level abstractions [67]. In the case study described by Ambler [91], an initial lack of refactoring led to the need of re-implementing the whole system after the number of users had grown drastically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors reported on advantages of constant code refactoring: ensuring readability and understandability of the code [82], improving modularity [80] and providing discipline to developers [93]. On the other hand, introducing refactoring may cause problems since developers had no or little experience [63] and they didn't see immediate value in introducing high level abstractions [67]. In the case study described by Ambler [91], an initial lack of refactoring led to the need of re-implementing the whole system after the number of users had grown drastically.…”
Section: Discussionmentioning
confidence: 99%
“…In the case study described by Ambler [91], an initial lack of refactoring led to the need of re-implementing the whole system after the number of users had grown drastically. Finally some authors reported work practices related to deployment claiming that some software teams deploy manually the code on the infrastructure [67] while others rely on continuous integration tools [93].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations